Acinetobacter species as pathogens in tertiary care hospital - A retrospective study - Sonali Budhagaonkar, M.B. Nagmoti*, Jyoti.M.Nagmoti and (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Acinetobacter species are gaining importance in the present days. Here we report isolation of 149 isolates of Acinetobacter species from various clinical samples from the intensive units of our hospital. We used standard microbiological techniques to identify the isolates and antibiotic sensitivity testing was done by using Kirby-Bauer disc diffusion technique. A.baumanii was the commonest organism in our study and was found multi drug resistant. Ã‚Â 